Parto humanizado en mujeres de etnia indígena: Visión Intercultural. - Noguera Jaramillo, Nohelya Isabel (2025)
Humanized childbirth among Indigenous women represents an ancestral practice that promotes respect for autonomy and human dignity. Its significance lies in integrating traditional knowledge with the principles of intercultural healthcare, recognizing childbirth as a natural, spiritual, and social event. The objective of this study was to analyze the importance of humanized childbirth among women of Indigenous ethnicity, taking into account their worldview and the intercultural approach. The methodology consisted of a systematization of research reports through a bibliographic review conducted from a qualitative, descriptive, and analytical perspective. Seventy scientific documents were reviewed, and after applying inclusion and exclusion criteria, a final sample of 48 bibliographic sources was obtained, all published between 2020 and 2025 in Google Scholar and indexed journals such as PubMed, Scielo, and Redalyc. In Indigenous communities of Ecuador, Peru, Chile, and Colombia, childbirth is carried out through upright birthing practices that include the use of medicinal plants, symbolic management of the placenta and umbilical cord, and purification rituals. Family accompaniment plays a central role, supporting the exercise of reproductive rights and strengthening intercultural healthcare. All in all, intercultural childbirth promotes the humanization of healthcare, strengthens women’s empowerment, and preserves ancestral knowledge by bridging evidence-based medicine with traditional approaches. This integration contributes to safe, respectful, and culturally appropriate care within Indigenous communities.